THE INFLUENCE OF TRANSFORMASIONAL LEADERSHIP, THE GROW ME COACHING MODEL, AND WORK MOTIVATION ON TEACHERS’ INSTRUCTIONAL INNOVATION IN ELEMENTARY SCHOOLS OF BULU DISTRICT REMBANG - Safikin; Rasiman; supandi (SOSIOEDUKASI, 2025)
This study aims to examine the influence of transformational leadership, the GROW ME coaching model, and work motivation on teachers’ instructional innovation in public elementary schools in Bulu District, Rembang Regency. Employing a quantitative approach with a survey design, data were collected from 103 teachers across 18 schools using validated questionnaires. The results of descriptive analysis indicate that all three independent variables are in the “high” category, while instructional innovation also falls into the “high” category. Multiple regression analysis reveals that transformational leadership (β = 0.300, p < 0.05), the GROW ME coaching model (β = 0.266, p < 0.05), and work motivation (β = 0.322, p < 0.05) each have a positive and significant effect on instructional innovation. Among them, work motivation shows the greatest influence. Simultaneously, the three variables contribute 54.2% to variations in instructional innovation, while the remaining 45.8% is influenced by other factors not examined in this study. The novelty of this research lies in the integrated analysis of leadership, coaching, and motivation variables within the elementary school context, providing practical implications for improving teaching quality through innovation-oriented strategies.